2010
DOI: 10.1143/jjap.49.026501
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Effect of Conditioner Aggressiveness on Removal Rate during Interlayer Dielectric Chemical Mechanical Planarization through Confocal Microscopy and Dual Emission Ultraviolet-Enhanced Fluorescence Imaging

Abstract: The effect of conditioner aggressiveness is investigated in interlayer dielectric polishing on three types of pad. A method using confocal microscopy is used to analyze the effect of conditioner aggressiveness on pad–wafer contact. Results show that a more aggressive conditioner produces a higher interlayer dielectric polishing rate while at the same time a pad surface with fewer contacting summits and less contact area. It is found that the ratio of the contacting summit density to the contact area fraction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
69
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(71 citation statements)
references
References 15 publications
2
69
0
Order By: Relevance
“…Such a study is important because previously published works have shown that the pad surface micro-texture has important effects in CMP such as material removal rate, within-wafer-nonuniformity and wafer-level defects. (4)(5)(6)(7)(8)(9)(10)…”
Section: Introductionmentioning
confidence: 99%
“…Such a study is important because previously published works have shown that the pad surface micro-texture has important effects in CMP such as material removal rate, within-wafer-nonuniformity and wafer-level defects. (4)(5)(6)(7)(8)(9)(10)…”
Section: Introductionmentioning
confidence: 99%
“…11 Elmufdi et al and Muldowney et al showed that pad surface with higher contact area could reduce CMP-related defects since higher contact area induces lower local pressure to the wafer. 12,13 As Ting et al 10 found that a more aggressive disk creates pad surface with less contact area, the more aggressive diamond disk is expected to generate more defects during CMP processes. In this study, aggressive diamonds are identified for two perpendicular disk orientations.…”
Section: Resultsmentioning
confidence: 99%
“…3,4) Sun et al employed laser confocal microscopy to measure the pad surface contact area as well as pad surface topography and studied the relation between contact area and contact summit density under different pressures. 5,6) In a recent study, 10) 200-mm blanket copper wafers were polished and the polishing results were correlated to the pad surface contact area and topography. It was found that higher near contact area induced by the fractured and collapsed pore walls plays a significant role in lowering the coefficient of friction (COF) and removal rate during Cu CMP.…”
mentioning
confidence: 99%
“…Most of these studies found that higher contact area leads to lower removal rate due to the lower local contact pressure. 6,[20][21][22] In this study, pad surface contact area percentages are calculated and their values are 0.040 and 0.011% at the conditioning forces of 26.7 and 44.5 N, respectively. Recall that average removal rates are 2,015 and 3,288 A/min at the conditioning forces of 26.7 and 44.5 N, respectively.…”
mentioning
confidence: 99%